Microalgae Cultivation and Its Potential for Phycoremediation Agent - Imroatin Sakinah Rahmatina; Harmin Sulistiyaning Titah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Microalgae can be an ecological remediation agent known as phycoremediation. Understanding these factors is critical in producing the expected products efficiently. Several factors affect microalgae growth, including nutrients, temperature, pH, CO2 concentration, lighting, microalgae photosynthesis processes, and hydrodynamic factors. Microalgae Chlorella vulgaris has the potential to survive in media contaminated with heavy metal and high salinity levels. It can reduce the concentration of heavy metals in water through several mechanisms. Further research must be conducted to determine the factors influencing microalgae growth. The research was conducted to observe the growth rate of microalgae in a controlled photobioreactor. The cultivation was carried out in a plastic photobioreactor equipped with aeration, lighting, and the addition of nutrients. The first stage of the research was observations on C. vulgaris growth with 30% inoculum and 20% inoculum. The C. vulgaris growth rate is 0.133 cells/mL/day and 0.927 cells/mL/day, respectively. The second stage of the research was observations on C. vulgaris growth with 20‰ salinity, and the variation used is the aeration, 3 L/min, and 4 L/min. The C. vulgaris growth rate is 0.263 cells/mL/day and 0.236 cells/mL/day, respectively.